Internal wave detection and wavelength estimation. - Marghany, Maged
The utility of wavelet analysis was examined using two-dimensional (2-D) wavelet transform for internal wave detection and wavelength estimation. The continuous wavelet transform was also used to estimate energies and wavelengths within soliton peaks from the detect internal wave. The Doppler radar was used to estimate the speed of the internal wave. It was found that the integration between wavelet transform and Doppler model is an excellent tool to detect internal wave. The polarized L-band was more suitable for detection of internal wave compared to C-band. The isothermal profile of the internal wave suggested that the irregular bottom topography and tidal flow are a main reason for generating internal waves in South China Sea.